2021
DOI: 10.7150/thno.58421
|View full text |Cite
|
Sign up to set email alerts
|

The utility of biomedical scaffolds laden with spheroids in various tissue engineering applications

Abstract: A spheroid is a complex, spherical cellular aggregate supporting cell-cell and cell-matrix interactions in an environment that mimics the real-world situation. In terms of tissue engineering, spheroids are important building blocks that replace two-dimensional cell cultures. Spheroids replicate tissue physiological activities. The use of spheroids with/without scaffolds yields structures that engage in desired activities and replicate the complicated geometry of three-dimensional tissues. In this mini-review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 108 publications
0
58
0
Order By: Relevance
“…This is probably due to the fact that cells in 3D culture experience a heterogeneous environment in regards to nutrient supply, oxygen availability, and waste disposal which is ultimately dictated by spheroid size. 22,45,48,49 As cell number increases, poor oxygenation and nutrient depletion lead to the formation of a necrotic core. 9,28,45,50 It has been suggested that the limit of oxygen diffusion in vivo is 200 µm with poor conditions found at the core of spheroids larger than 400 µm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the fact that cells in 3D culture experience a heterogeneous environment in regards to nutrient supply, oxygen availability, and waste disposal which is ultimately dictated by spheroid size. 22,45,48,49 As cell number increases, poor oxygenation and nutrient depletion lead to the formation of a necrotic core. 9,28,45,50 It has been suggested that the limit of oxygen diffusion in vivo is 200 µm with poor conditions found at the core of spheroids larger than 400 µm.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,6,8,9,[18][19][20][21] They also have higher levels of tissue-specific gene expression and increased exosome production. 10,22 Overall, spheroids enhance biological processes relating to immunity, inflammation, angiogenesis, and wound healing. 14,[23][24][25][26] A previous study by Murphy et.…”
Section: Introductionmentioning
confidence: 99%
“…Although spheroids were not widely explored in AF tissue engineering, recent developments expanded the possibilities for spheroid-biomaterial seeding in related areas of musculoskeletal repair. In bone tissue engineering, foaming/freeze-drying techniques were used to produce scaffold microporosity that promoted spheroid penetration into the scaffold and fixed them in place [ 16 , 17 ]. Spheroids were also generated in situ in a novel porous PLGA/CS scaffold obtained after lyophilization.…”
Section: Spheroid-based Cell Therapies For Degenerative Disc Diseasementioning
confidence: 99%
“…Recent developments in other fields of tissue engineering demonstrate that spheroid-based approaches could help overcome some of these challenges due to their superior regenerative performance and/or resistance when compared to single cells [ 16 , 17 ]. Spheroids are self-assembling living microtissues based on multicellular aggregates that mature by the formation of intercellular contacts on non-adhesive substrates [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation